Cover Feature: A Broader‐scope Analysis of the Catalytic Reduction of Nitrophenols and Azo Dyes with Noble Metal Nanoparticles (ChemCatChem 11/2019). Issue 11 (6th June 2019) - Shultz, Lorianne R.; Hu, Lin; Preradovic, Konstantin; Beazley, Melanie J.; Feng, Xiaofeng; Jurca, Titel
Abstract : The Cover Feature shows the reduction of para ‐nitrophenol over a selection of carbon‐supported noble‐metal nanoparticles. In their Communication, Beazley, Feng, Jurca and co‐workers survey the catalytic reduction of a broad scope of nitrophenols and azo dyes by Au, Ag, Pt, and Pd nanoparticles supported on amorphous carbon. By screening catalysts beyond the para ‐nitrophenol reaction, it becomes clear that this broadly utilized standard model system is not an ideal prognosticator of catalytic activity. Alternatively, incorporating aminonitrophenols into the screening protocol leads to better predictions of activity, evidenced by trends observed in the reduction of azo dyes. More information can be found in the Communication by L. R. Shultz et al. on page 2590 in Issue 11, 2019 (DOI: 10.1002/cctc.201900260 ).